35M MAX: the first bus rapid transit system in Salt Lake County. (15th February 2010) - Zlatkovic, Milan; Stevanovic, Aleksandar; Cevallos, Fabian; Johnson, Hal Ryan
Bus rapid transit (BRT) is becoming one of the most popular transit services in the USA. A total of 106 miles of BRT service is scheduled for deployment in the State of Utah in future years. This research looked at the first BRT deployment in West Valley City, Salt Lake County, Utah. The 10.8 miles long BRT line was launched on July 14, 2008, and shortly after the launching the first operational data became available. In addition, a series of surveys were conducted to gain feedback from the users of the BRT system. Preliminary results show significant improvements in transit operations, with a 33% increase in ridership, reductions of close to 15% in travel times and improved reliability. Survey results show a high degree of acceptance among the system users. In general, the BRT system has proven itself to be very successful, bringing significant improvements to transit riders.